Lichen Planus − the role of the general dental practitioner. (2nd June 2019) - Dawoud, Basim ES; Mohamed, Samira H; Wareing, Jonathan
Abstract : Oral lichen planus is frequently encountered in primary and secondary dental care. The soft tissues of the mouth should always be examined carefully at check-ups and any abnormality be palpated to detect change in consistency (induration) along with any changes in colour or general appearance. Such changes should prompt a referral for specialist review. CPD/Clinical Relevance: The general dental practitioner (GDP) can play a simple yet effective role in the management of lichen planus by removing obvious traumatic stimuli, improving oral hygiene and advising on simple topical treatment.